PENGEMBANGAN FORMULASI MIKROEMULSI MINYAK SEREH (Cymbopogon nardus) MENGGUNAKAN EMULGATOR SURFAKTAN NONIONIK - A Hasrawati; Nursiah Hasyim; Nur Alif Irsyad (Jurnal Fitofarmaka Indonesia, 2016)
Citronella oil (Cymbopogon nardus) is an essential oil which useful as an antibacterial that is usuallyprovided in the form of macroemulsion for topical use. absorption of macroemulsion through the skin relatively low, thermodynamically is not stable and can produce a separate phase in the storage period. The one of development emulsion  system  to  get  better  characteristics  is  to  form  a  microemulsion.  Microemulsion  is  an  oil  and  water dispersion stable thermodynamically stabilized by surfactants and in some cases a cosurfactant. The objective of this study was to formulatecitronella oil in the form of a stable microemulsion using nonionic surfactant. Optimization of the type and amount of emulsifier (surfactant) was required to formulate a stable microemulsion. In this study, microemulsion was evaluated during a month. Type   and concentration of surfactant, cosurfactant, Citronella oil (Cymbopogon nardus) and water was optimized. A stable citronella oil microemulsion was successfully created with composition of 15% PEG 400 as cosurfactant, 15% tween 80 as surfactant, 2-4% Citronella oil as oil phase and 10% glycerin as humectant and distilled water as aqueous phase. From the observation, microemulsion formula has   clear appearance but  physically unstable during a month storage